Community Health Centers and Access to Care Among Underserved Populations: A Synthesis Review. (February 2020) - Saloner, Brendan; Wilk, Adam S.; Levin, Jonathan
Community health centers (CHCs) deliver affordable health services to underserved populations, especially uninsured and Medicaid enrollees. Since the early 2000s, CHCs have grown because of federal investments in CHC capacity and expansions of Medicaid eligibility. We review 24 relevant studies from 2000 to 2017 to evaluate the relationship between CHCs, policies that invest in services for low-income individuals, and access to care. Most included studies use quasi-experimental designs. Greater spending on CHCs improves access to care, especially for low-income and minority individuals. Medicaid expansions also increase CHC use. Some studies indicate that CHC investments complement Medicaid expansions to increase access cost-effectively. Further research should explore patient preferences and patterns of CHC utilization versus other sites of care and population subgroups for which expanding CHC capacity improves access to care most. Researchers should endeavor to use measures and sample definitions that facilitate comparisons with other estimates in the literature.